Replacement of Belt Structure for FEA of Tire. (2016) - Krmela, Jan; Krmelová, Vladimíra
Abstract: The paper deals with computational modeling of radial tire for cars. The authors used FEA (Finite Element Analysis) utilizing program ANSYS. The authors are oriented not only to the strain-stress analyses of tire. In relation to the tire computational models, the composite structure parts (textile carcass, steel-cord belt and textile belt) cannot be implemented up to the level of reinforcing cords because of the time difficulty as well as the large number of the finite elements. The composite structure parts are partially replaced with some specified stiffness. The paper describes the different ways of replacement of structure represented by the steel-cord belt. These replacements are used for FEA of tire.